Matharpacady-24.jpg - Mumbai Archive Project Team (Jio Institute, 2024)
Ladies strike a conversation on the veranda at Keep Sake, 20 Matharpacady (built in 1928). The tightly spaced bungalows enable residents to interact with each other and socialize on the veranda. The long veranda is a typical feature of Koli villages where the open space at the front is used to repair fishing nets. This common characteristic is also seen in the bungalows of the East Indian community, whose ancestors were Kolis and other native communities before they were converted to Catholicism.